Bupivacaine in alginate and chitosan nanoparticles: An in vivo evaluation of efficacy, pharmacokinetics, and local toxicity - Cereda, Cíntia Maria Saia; Mecatti, Daniel Sebbe; Papini, Juliana Zampoli Boava; Bueno, Diego Valério; Franz-Montan, Michelle; Rocha, Thalita; Júnior, José Pedrazzoli; de Paula, Eneida; de Araújo, Daniele Ribeiro; Grillo, Renato [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Calafatti, Silvana Aparecida; et al. (Taylor & Francis, 2018)
Objective: This study reports a preclinical evaluation of an alginate/chitosan nanoparticle formulation containing NovaBupi®, a racemic bupivacaine (BVC) containing 25% dextrobupivacaine and 75% levobupivacaine. Methods: New Zealand White rabbits (n=6) received intraoral or intrathecal injections of BVC 0.5% or BVC 0.5%-loaded alginate-chitosan nanoparticles (BVCALG). BVC plasma levels and pharmacokinetic parameters were determined in blood samples of these rabbits. An infraorbital nerve blockade was performed in male Wistar rats (n=7) with the same formulations and the vehicle (NPALG). Histological evaluation of local toxicity after 6 hours and 24 hours of the treatments was performed in rats’ (n=6) oral tissues. Results: No statistically significant difference was observed between plasma concentrations and pharmacokinetic parameters (p>0.05) after intraoral injections. However, after intrathecal injection BVCALG changed approximately three times the values of volume of distribution and area under the curve (AUC0-t; p<0.05). The total analgesic effect of BVC after infraorbital nerve blockade was improved by 1.4-fold (p<0.001) with BVCALG. BVC and BVCALG did not induce significant local inflammatory reaction. Conclusion: The encapsulation of BVC prolongs the local anesthetic effect after infraorbital nerve blockade and altered the pharmacokinetics after intrathecal injection.
Keywords: Bupivacaine; Drug delivery; Local anesthetics; Polymeric nanoparticle; Preclinical study